PSYCHOLOGICAL AND ETHICAL ASPECTS OF THE INTERPRETATION PROCESS - Sydoruk, G.I. (Proceedings of National Aviation University (archive), 2005)
Specific psychological and ethical features of the interpretation activity, contributing to interpreting at the acceptable level, are considered. Linguistic abilities, the interpreter’s psychological features, knowing culture and ethics of interpretation and communication would be advantageous in creating his positive image and successful performance. Some recommendations on these subject matters are given. The interpreter should adequately estimate his linguistic and interpretation limitations and possibilities. Specific attention is paid to appearance, dressing, health issues, habits, and cultural differences, manifested in behavior. Apart from being aware of his rights and duties, interpreter should know his don’ts. All these issues are resolved at practical classes.